A Critical Discourse Analysis on Gender Inequality in “Impatient For Change: Global Action Gender Equality” Speech by Phumzile Mlambo-Ngcuka on UN Women Executive Board - E, Anisha; Irawan, Andi Muhammad (English Language and Literature, 2024)
Critical Discourse Analysis (CDA) is a common method utilized in numerous research which is an analysis used to critique political speech. The purpose of this study is to find out discourse topics and discourse strategies presented by Phumzile Mlambo-Ngcuka to reveal her arguments about Gender Equality in her speech entitled “Impatient for Change: Global Action Gender Equality”. The method used in this study was a descriptive qualitative approach. Further, this study utilised information from Phumzile Mlambo-Ngcuka’s speech “Impatient for Change: Global Action Gender Equality” and concentrated on the topic of gender inequality. The findings of the study revealed that: (a) there were 4 discourse topics found: ‘Impatience for Gender Equality’ 9 times (45%), ‘The Challenges for Gender Equality’ 4 times (20%), ‘Women’s full participation in peace processes and negotiations’ 3 times (15%), and ‘Gender equality is not only the work of UN Women’ 4 times (20%), and (b) there were 7 discourse strategies found: Burden 6 times (30%), Lexicalization 6 times (30%), Implication 2 times (10%), and Presupposition 3 times (15%), Hyperbole 1 time (5%), Disclaimer 1 time (5%), and Illustration 1 time (5%).